The endoplasmic reticulum-associated mRNA-binding proteins ERBP1 and ERBP2 interact in bloodstream-form Trypanosoma brucei - Bajak, Kathrin; Leiss, Kevin; Clayton, Christine; Erben, Esteban D. (PeerJ, 2020)
Kinetoplastids rely heavily on post-transcriptional mechanisms for control of gene expression, and on RNA-binding proteins that regulate mRNA splicing, translation and decay. Trypanosoma brucei ERBP1 (Tb927.10.14150) and ERBP2 (Tb927.9.9550) were previously identified as mRNA binding proteins that lack canonical RNA-binding domains. We show here that ERBP1 is associated with the endoplasmic reticulum, like ERBP2, and that the two proteins interact in vivo. Loss of ERBP1 from bloodstream-form T. brucei initially resulted in a growth defect but proliferation was restored after more prolonged cultivation. Pull-down analysis of tagged ERBP1 suggests that it preferentially binds to ribosomal protein mRNAs. The ERBP1 sequence resembles that of Saccharomyces cerevisiae Bfr1, which also localises to the endoplasmic reticulum and binds to ribosomal protein mRNAs. However, unlike Bfr1, ERBP1 does not bind to mRNAs encoding secreted proteins, and it is also not recruited to stress granules after starvation.
Gesehen am 26.03.2020